Study of a novel environmental friendly frother in coal flotation. Issue 1 (2nd January 2020) - Cheng, Yali; Fu, Xiaoheng; Yan, Siqin; Liu, Jinting; Shi, Xu; Huang, Zijian
ABSTRACT: A novel environmental friendly frother FA-803 was selected and compared with other three kinds of frother commonly used in coal preparation plants. It was observed that there was a relationship between the combustible material recovery with the same amount of collector and different amounts of frother and the water-carrying rate of flotation froth. When the concentration of frother was less than 20 ul/L (volume of coal slurry), there was a good linear relationship between the combustible material recovery and water-carrying rate. The higher the water-carrying rate, the higher the combustible recovery. As the concentration of frother increased, it increased the recovery rate of water. At the same time, the flotation results also showed that the foam stability of frother was different because of the different polarity. Frother FA-803 with good foam stability can achieve high combustible recovery at low concentration.